2019
DOI: 10.11118/actaun201967061597
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Volatility and Dynamic Relation Between Stock Market, Exchange Rate and Select Commodities

Abstract: Commodities play a vital role in the development of emerging economies, like India. From this perspective, the study presents dynamic correlation in the prices of gold, crude oil, exchange rate and Indian stock market from April 01, 2014 to March 28, 2018. VARMA-BEKK-GARCH model is estimated for return and volatility spillovers across markets. Bidirectional returns spillover was found between Nifty and WTI and WTI and Gold pair. Whereas the bidirectional volatility spillover between Nifty and Gold pair. From t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Syahri and Robiyanto (2020) used the Dynamic Conditional Correlation Generalized Autoregressive Conditional Heteroskedasticity (DCC-GARCH) approach to investigate the correlation between gold, exchange rate, and stock during the COVID-19 pandemic in Indonesia. Siddiqui and Roy (2019) utilized the same method to look at the dynamic connection between the Indian stock index and the currency rate. These researches revealed that stock markets and currency rates have a conditional relationship over time.…”
Section: Introductionmentioning
confidence: 99%
“…Syahri and Robiyanto (2020) used the Dynamic Conditional Correlation Generalized Autoregressive Conditional Heteroskedasticity (DCC-GARCH) approach to investigate the correlation between gold, exchange rate, and stock during the COVID-19 pandemic in Indonesia. Siddiqui and Roy (2019) utilized the same method to look at the dynamic connection between the Indian stock index and the currency rate. These researches revealed that stock markets and currency rates have a conditional relationship over time.…”
Section: Introductionmentioning
confidence: 99%
“…Siddiqui and Roy (2019), D. Huang and Kilic (2019), Balcilar, Demirer, Gupta, and Wohar (2020), Kang, Yoon, Bekiros, and Uddin (2020), Vikneswaran, Purdasy, Rashid, and Basirduddin (2020), and Cheema and Szulczuk (2020) tested various commodities as hedging assets. Siddiqui and Roy (2019) show that gold is a more effective hedging asset than crude oil for institutional investors in India. D. Huang and Kilic (2019) show that gold prices fall in recessions, although to a lesser extent than platinum prices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As far as is known, this essay is the first study that analyzes the rebalancing of portfolios in the context of the global pandemic . Additionally, we are aware that the authors Balcilar, Hammoudeh, and Asaba (2015), Siddiqui and Roy (2019), Hussain Shahzad, Bouri, Roubaud, and Kristoufek (2020), Vikneswaran, Purdasy, Rashid, and Basirduddin (2020), analyzed gold as a safe haven for rebalancing of portfolios, but the markets, research questions, and approach were different from those followed in this essay. In terms of structure, this essay is organized in five sections.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Laily et al (2017) show a positive relationship between crude oil prices, and the price of gold, and a negative synchronization between inflation rate, GDP, interest rates, and exchange rates. Tursoy and Faisal (2018), Siddiqui and Roy (2019), D. Huang and Kilic (2019) examined the importance of gold as a safe risk hedging asset. Tursoy and Faisal (2018) show a negative relationship between the price of gold and stock prices and a positive relationship between crude oil and stock prices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tursoy and Faisal (2018) show a negative relationship between the price of gold and stock prices and a positive relationship between crude oil and stock prices. Siddiqui and Roy (2019) show that gold is a more effective hedging asset than crude oil for institutional investors in India. D. Huang and Kilic (2019) demonstrate that gold prices fall into recessions, although to a smaller extent than platinum prices.…”
Section: Literature Reviewmentioning
confidence: 99%